Empathy Modulates the Effect of Stress Reactivity on Generous Giving - Azulay, Hagar; Guy, Nitzan; Pertzov, Yoni; Israel, Salomon (Frontiers in Neuroscience, 2022)
How does acute stress influence the degree to which we cooperate with others? Research on the effects of stress on social decision-making is guided by two seemingly contrasting theories. Acute stress may trigger a Fight-or-Flight response, manifested by increased anxiety, and more egocentric or selfish behavior. Alternatively, according to the Tend-and-Befriend model, acute stress may induce affiliative behaviors, marked by increased prosociality in an effort to seek and receive social support and protection. Extant studies on the topic do not provide consistent support for either pattern of behavior, with studies showing evidence for both Fight-or-Flight or Tend-and-Befriend like responses. One possibility, may be the nature of social responses to stressful situations differ as a function of the individual. In the current study, we demonstrate an example of such a person-by-situation interaction, showing that acute stress can cause either pro-social or selfish responses, contingent on individual differences in trait empathy. One hundred and twenty three participants (60 F) were assessed for trait empathy using the Interpersonal Reactivity Index; consequently, they underwent either the Trier Social Stress Test—a well-validated paradigm for eliciting acute psychosocial stress—or a non-stress inducing control condition. Following exposure to either the stress or control condition, participants played a one-shot Dictator Game to evaluate their generosity levels. Statistical analyses revealed that acute stress by itself did not affect the amount transferred in the Dictator Game. Rather, individual differences in trait empathy moderated the effects of stress on giving. Elevations in stress-induced cortisol resulted in more generous behavior, but only in individuals high in empathy. In contrast, in individuals low in empathy, a greater rise in stress-induced cortisol resulted in more selfish behavior. Effects were more pronounced in females than males. Our findings highlight the necessity of integrating personality traits as important moderators of the link between stress and sociality.